2008
DOI: 10.1002/da.20463
|View full text |Cite
|
Sign up to set email alerts
|

Hypofrontality in panic disorder and major depressive disorder assessed by multi-channel near-infrared spectroscopy

Abstract: This study clarified that hypofrontality in panic disorder is evident even with neutral stimuli of little emotional load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 27 publications
(51 reference statements)
3
39
1
Order By: Relevance
“…34 Recent fMRI studies have demonstrated robust activation by the WFT in the left Brodmann's area (BA) 44/45, as well as adjacent BA46 and BA47, together with the premotor cortex (BA6) and insula. 35 Previous studies using NIRS [23][24][25][26] demonstrated bilateral frontal activation during the WFT in healthy controls, suggesting that not only the left, but also the right frontal lobe may play crucial roles in voluntary speech intention and/or attentional resources required for performing the WFT. Interconnected areas such as these are believed to participate in a functional language network subserving word output.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…34 Recent fMRI studies have demonstrated robust activation by the WFT in the left Brodmann's area (BA) 44/45, as well as adjacent BA46 and BA47, together with the premotor cortex (BA6) and insula. 35 Previous studies using NIRS [23][24][25][26] demonstrated bilateral frontal activation during the WFT in healthy controls, suggesting that not only the left, but also the right frontal lobe may play crucial roles in voluntary speech intention and/or attentional resources required for performing the WFT. Interconnected areas such as these are believed to participate in a functional language network subserving word output.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of previous studies of activation in major depression using NIRS. [23][24][25][26] Neuropsychological studies of patients with lesions in the left prefrontal areas have revealed impairment of word list generation, suggesting the importance of the prefrontal areas for WFT. 34 Recent fMRI studies have demonstrated robust activation by the WFT in the left Brodmann's area (BA) 44/45, as well as adjacent BA46 and BA47, together with the premotor cortex (BA6) and insula.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations